PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM MENINGKATKAN KUALITAS PEMILU SERENTAK TAHUN 2024 - Nuraida Nuraida; Priska Nurlia Br Simanungkalit2 (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The holding of elections in Indonesia is a form of implementation of people's sovereignty which is useful for electing prospective leaders to improve the welfare of the people. The use of Artificial Intelligence (AI) is a crucial choice in the implementation of simultaneous elections in 2024 which will be useful for providing convenience and expediting the election process so as to improve the quality of the 2024 simultaneous elections and encourage people's participation in the election process. This study uses a literature study by analysing various sources such as books, journals and others. The results of the study explain that the use of Artificial Intelligence (AI) in improving the quality of simultaneous elections in 2024 in the form of facilitating elections to be more efficient, accurate, effective and more transparent and able to increase proficiency and professionalism in preventing errors.